Outcome measures for children with movement disorders. (May 2018) - Pagliano, Emanuela; Baranello, Giovanni; Masson, Riccardo; Foscan, Maria; Arnoldi, Maria Teresa; Marchi, Alessia; Aprile, Giorgia; Pantaleoni, Chiara
Abstract: The huge contribution of advances in the pediatric neurosciences, improvements in clinical practice, and new therapeutic options, has led to the development of new models of treatment and rehabilitation for dystonia in the last decade. It is now generally agreed that a multidimensional therapeutic approach is needed for children with motor disorders, whose motor function-conceived as a complex perceptive, motor and cognitive process - is impaired at a crucial time in their development, with a fall out on how their various adaptive functions evolve. Neurophysiological studies, modern neuroimaging techniques, and advances in cognitive psychology have all contributed to improving our understanding of the potential effects of treatments in early age - not only on the symptoms, but also on plasticity processes and neuronal reorganization. The International Classification of Functioning, Disability and Health (ICF) promoted by the WHO, and the diffusion of family-centered models of healthcare have underscored the importance of the ecological perspective with a view to providing effective therapies and a satisfactory quality of life for dystonic children and their families. The advances made in this area have made it necessary to study and develope more appropriate treatment outcome measures. In the light of these aspects, there is still not enough literature on the generally-accepted, exhaustive dystonia assessment tools. Given these limits, it might be useful to discuss the strengths and weaknesses of the main tools currently used in this setting. Highlights: The assessment and treatment of childhood dystonia are still not well defined. In this review we discuss the strengths and weaknesses of the main outcome measures currently used. It is necessary to have a "toolbox" of the outcome measures capable of assessing various aspects and dimensions of life.